The Influence of Perceived Values and Culture on the Well-Being of Malaysians - Zainudin, Mohamad Zahir; Zaini, Zaki; Kamarudin, Mohd Fauzi (Journal of Human Capital Development (JHCD), 2021)
ABSTRACT Quality of life is used as a method to determine the level of well-being in a society. Since quality of life is subjective, it is determined by a variety of factors and one of the factors is perception. This study is to identify the relationship between ethnicity, education level and income among households towards their quality of life. The research methodology used are document analysis, individual and group interviews, as well as direct observation. In this study, Indian ethnicity showed higher perception of quality of life than other ethnicities. The findings also show that the level of tertiary education and income status encourage positive perceptions of the family environment and cultural values. Based on the three findings of this study, this study concludes that family environment influences the perception of ethnicity, education level and income of Malaysians on their quality of life. Keywords: Quality of life, environment, cultural values, ethnicity, income